TAMUS (Ta'lim Musaghar): Augmented Reality-Based Speaking Platform to Improve the Maharah Kalam for Arabic Language Education Students - Fahraini, Sovia; Almaliki, Muhammad Fikri (Proceeding International Conference on Religion, Science and Education, 2024)
The problem of Arabic language education study program students' low level of maharah kalam or speaking ability has become a very important challenge in itself. Because, not all Arabic language education students have Arabic language skills at the previous level of education. And what is unique about Arabic is that it is different from English, which is used in a foreign society, so it is difficult to find native speakers or interlocutors to practice their Arabic speaking skills. This problem must be solved to create a better future for improving the speaking skills of Arabic language education students. With the aim of producing Arabic language education graduates who are competent, especially in speaking skills as the main component as foreign language graduates. Therefore, the aim of this research is to overcome the problem of maharah kalam ability by utilizing a speaking platform via augmented reality (AR) to offer learning with native speakers via augmented reality-based video calls, and how TAMUS (Ta'lim Musaghar) became a concept new ones that can be used as learning media independently. So that students feel that they are actually dealing directly with native speakers to carry out conversations using Arabic. This article uses a conceptual research design, specifically conceptual models and specifically uses conceptual descriptions. This article is important for academics to support literature reviews as a reference for their empirical research. The findings show that TAMUS is a new concept for an AR-based application to improve students' emotional skills.